2014
DOI: 10.1002/ajhb.22560
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of facial morphology between Okinawa Islanders and mainland Japanese using three‐dimensional images

Abstract: Objectives: Differences in facial height and breadth between Okinawa Islanders and mainland Japanese have been reported in previous craniometric and somatometric studies. This study using three-dimensional (3D) images aimed to identify more detailed characteristics of facial morphology in each population.Methods: Using a hand-held 3D scanner, we obtained 60 facial surface images each from Okinawa Islanders and mainland Japanese. Twenty-one landmarks were plotted on a computer and 27 measurements of distances a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
2
9
1
Order By: Relevance
“…In this study, it was confirmed that the Ryukyuan people have a smaller height in the upper and midfacial region compared with the mainland Japanese; it was also confirmed that the height of the lower face was almost identical between the two groups (Pietrusewsky, 1999;Dodo et al, 2000;Fukase et al, 2012;Miyazato et al, 2014). Less prominent nasal bones (rhinion) were observed in the Ryukyuan females; this finding corresponded to previous findings regarding male crania from the early-modern period where more detailed analyses had revealed that the Ryukyuans have nasal bones curved on the sagittal section (Fukase et al, 2012).…”
Section: Known and Novel Findingssupporting
confidence: 67%
See 4 more Smart Citations
“…In this study, it was confirmed that the Ryukyuan people have a smaller height in the upper and midfacial region compared with the mainland Japanese; it was also confirmed that the height of the lower face was almost identical between the two groups (Pietrusewsky, 1999;Dodo et al, 2000;Fukase et al, 2012;Miyazato et al, 2014). Less prominent nasal bones (rhinion) were observed in the Ryukyuan females; this finding corresponded to previous findings regarding male crania from the early-modern period where more detailed analyses had revealed that the Ryukyuans have nasal bones curved on the sagittal section (Fukase et al, 2012).…”
Section: Known and Novel Findingssupporting
confidence: 67%
“…Although a study of 3-D facial surface images indicated that the Ryukyuans have a larger glabellar protrusion than the mainland Japanese (Miyazato et al, 2014), our findings did not detect this difference based on any single measurement, probably because we used different baselines and because females have less distinctive features than males. However, results from our multivariate analyses may have suggested such a characteristic in the Ryukyuans; specifically, the glabella' t-radius (#102) showed a relatively large negative correlation at a loading of -0.577 with PC5, and PC5 showed smaller scores in Ryukyuan females than in mainland females; notably, the loadings for nasion' t-radius (#98) and subnasale' t-radius (#101) were -0.385 and 0.057, respectively.…”
Section: Known and Novel Findingscontrasting
confidence: 50%
See 3 more Smart Citations